PENGARUH SOFTWARE CABRI 3D TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SMA PEKANBARU - Putri Wahyuni; Andini Dwi Rachmawati (Departemen Pendidikan Matematika, FPMIPA, UPI, 2022)
This study aims to see the effect of the Cabri 3d software on the mathematical critical thinking skills of SMA PGRI students in Pekanbaru in the 2021/2022 academic year on the material of the position of the line and the plane. This research is a quantitative study with a quasi-experimental method (quasi-experimental), with the population in this study being all students of class XII IPA PGRI PEKANBARU. The sample used is a saturated sample where class XII IPA 1 and XII IPA 2 are the research samples, which means that the entire population is the sample. The research design used was The Nonequivalent Post-Test Only Control Group Design. The data analysis technique used for the hypothesis is using the Mann Whitney u test with the results obtained a sig value of 0.00 0.05, so it can be concluded that there is an effect of Cabri 3d software on students' mathematical critical thinking skills. Keywords: Cabri 3d software, mathematical critical thinking skills, Geometry